Stability and Bifurcation Analysis in a Nonlocal Diffusive Predator-Prey Model with Hunting Cooperation (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we propose a diffusive predator-prey model withhunting cooperation and nonlocal competition. Under a rather general selection of the kernel function, we first study the stability of the positive equilibrium of the model. Then, we obtain the conditions which Hopf bifurcation andTuring bifurcation occur. Our results show that nonlocal competition playsan important role in determining the dynamics of the model.